2015
DOI: 10.1021/jacs.5b01446
|View full text |Cite
|
Sign up to set email alerts
|

A New Molybdenum Nitride Catalyst with Rhombohedral MoS2 Structure for Hydrogenation Applications

Abstract: Nitrogen-rich transition-metal nitrides hold great promise to be the next-generation catalysts for clean and renewable energy applications. However, incorporation of nitrogen into the crystalline lattices of transition metals is thermodynamically unfavorable at atmospheric pressure; most of the known transition metal nitrides are nitrogen-deficient with molar ratios of N:metal less than a unity. In this work, we have formulated a high-pressure route for the synthesis of a nitrogen-rich molybdenum nitride throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(155 citation statements)
references
References 56 publications
(117 reference statements)
9
135
1
Order By: Relevance
“…1–7 Nitride reactivity can be tuned with the appropriate transition metal ion to render this site either nucleophilic or electrophilic. High oxidation states, generally, can be stabilized with this type of motif and are known to participate in reactivity spanning various transformations 8 such as N-atom transfer reactions and nitrile-alkyne cross-metathesis, 9,10 and also to act as surface supports that engage in important industrial processes such as Haber–Bosch 1114 and hydrodenitrogenation and hydrodesulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…1–7 Nitride reactivity can be tuned with the appropriate transition metal ion to render this site either nucleophilic or electrophilic. High oxidation states, generally, can be stabilized with this type of motif and are known to participate in reactivity spanning various transformations 8 such as N-atom transfer reactions and nitrile-alkyne cross-metathesis, 9,10 and also to act as surface supports that engage in important industrial processes such as Haber–Bosch 1114 and hydrodenitrogenation and hydrodesulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…As a new layered molybdenum dinitride material, the bulk single-crystal MoN 2 was successfully synthesized in recent experiment. 22 Subsequent study has shown that a monolayer MoN 2 could be realized and its ground state has a strong ferromagnetic ordering with a Curie temperature above 420 K. 23 Here, based on first-principles calculations, we discover that the monolayer MoN 2 actually exhibits two stable isostructural phases with extremely dissimilar N-N distances along the perpendicular direction: the ߙ-phase of a large N-N distance (݀ N-N ≅ 2.20 Å), corresponding to the ground state structure discussed in the previous study; 23 and a new ߚ-phase of a much shorter N-N distance (݀ N-N ≅ 1.54 Å). We show that the key difference between the two phases is on the N-N bonding status: the ߙ phase is with a nonbonding N-N state; whereas the ߚ-phase is with a N-N single bond state.…”
mentioning
confidence: 99%
“…Diffraction peaks corresponding to Na x WO 3 (PDF#05‐0367) can be clearly identified, revealing that an oxidation‐reduction process between B 4 C and W 6+ has occurred to form Na x WO 3 . Only some very weak peaks of the reaction byproduct NaBO 2 are detected as it is rather air sensitive, which makes the Bragg reflections almost invisible in the pattern …”
Section: Resultsmentioning
confidence: 99%